First record of Red Drum Sciaenops ocellatus Linnaeus 1766 (Perciformes: Sciaenidae) in Campeche, Mexico - Wakida-Kusunok, Armando T.; Santos-Valencia, Josefina (Universidad Autónoma Metropolitana, 2017)
The presence of Sciaenops ocellatus in Campeche Mexico, in catches of small scale fishermen in Isla Arena, Campeche City and Champotón is reported. The probable source of this introduction is attributed to escape of specimens from aquaculture floating cages located in nearby of Seybaplaya and Isla Arena, Campeche. Further research is required to assess the ecological impacts of this exotic species in the zone. Se reporta la presencia de Sciaenops ocellatus en Campeche, México en las capturas de pescadores artesanales en Isla Arena, en la ciudad de Campeche y en Champotón. La posible fuente de introducción es atribuida a escapes de especímenes de jaulas de cultivo en zonas cercanas a Seybaplaya e Isla Arena. Es necesario realizar más investigación para estimar los impactos ecológicos de esta especie exótica en la zona.